REAKSI INVESTOR TERHADAP PENGUMUMAN LABA DAN UNEXPECTED EARNING PADA SEKTOR INFRASTRUKTUR SAAT MENGHADAPI KOS STICKINESS - Silvia Putri Faridayanti; Robiyanto Robiyanto (Magister Manajemen STIE Bank BPD Jateng, 2021)
The purpose of this study is to determine investors reactions to earnings announcements and unexpected earnings when facing stickiness cost. Sampling in this study used a purposive sampling technique with a total of 10 infrastructure companies listed on the IDX during 2015-2019. The analysis technique in this study uses panel regression analysis using EVIEWS 9. The results of this study indicate that there is no investor reaction to earnings announcements in infrastructure companies when there are low and high stickiness cost. However, when the company has a combined stickiness cost, there is an investor's reaction to the earnings announcement by seeing a positive CAR value which means good earnings quality. Unexpected Earning has no effect on companies that are facing stickiness cost, so the results of this study indicate that there is no investor reaction to unexpected earnings in infrastructure companies that have low, high, and combined stickiness cost. The conclusion of this study is that earnings information becomes less important in predicting future earnings.